2010
DOI: 10.1074/jbc.m110.152470
|View full text |Cite
|
Sign up to set email alerts
|

Charged or Aromatic Anchor Residue Dependence of Transmembrane Peptide Tilt

Abstract: The membrane-spanning segments of integral membrane proteins often are flanked by aromatic or charged amino acid residues, which may "anchor" the transmembrane orientation. Single spanning transmembrane peptides such as those of the WALP family, acetyl-GWW(LA) n LWWA-amide, furthermore adopt a moderate average tilt within lipid bilayer membranes. To understand the anchor residue dependence of the tilt, we introduce Leu-Ala "spacers" between paired anchors and in some cases replace the outer tryptophans. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
185
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 65 publications
(202 citation statements)
references
References 45 publications
17
185
0
Order By: Relevance
“…1c). The low mobility of GWALP23 had been noted before, namely in a comparison with WALP23 using fitted values of S zz in a GALA analysis (Vostrikov et al 2010). It was attributed to the presence of a single Trp residue at each end of the GWALP23 helix, as opposed to two consecutive Trp side-chains at each end in WALP23 (which is also the case of WLP23).…”
Section: Resultsmentioning
confidence: 93%
“…1c). The low mobility of GWALP23 had been noted before, namely in a comparison with WALP23 using fitted values of S zz in a GALA analysis (Vostrikov et al 2010). It was attributed to the presence of a single Trp residue at each end of the GWALP23 helix, as opposed to two consecutive Trp side-chains at each end in WALP23 (which is also the case of WLP23).…”
Section: Resultsmentioning
confidence: 93%
“…S1 and Table S1), we analyzed the helix tilt for each of the transmembrane peptides (21,23). (Although excessive peptide dynamics does complicate the determination of helix tilt for some peptides (24)(25)(26), the problem is mitigated and the dynamics become tractable when only two aromatic residues are present (3,21) and additionally when a polar residue is present (17,21). We therefore estimated the rather minimal dynamics of the K12 and K14 peptides using a principal order parameter (21).…”
Section: Resultsmentioning
confidence: 99%
“…GWALP23 | lysine titration | solid-state deuterium NMR T he basic residues lysine (Lys) and arginine (Arg) in membrane proteins are enriched at the interfacial region and are believed to assist in anchoring the transmembrane orientations (1)(2)(3). In the hydrophobic core of transmembrane proteins, these polar amino acids are significantly depleted because of the energetic cost of burying them in the nonpolar lipid environment.…”
mentioning
confidence: 99%
“…Asymmetric distribution of basic amino acids, with respect to the lipid bilayer, is a well known factor influencing membrane topology, as has been generalized in the "positive inside rule" of von Heijne (47), and may assist TM membrane insertion (48). Furthermore, Vostrikov et al (49) have shown that Arg, Gly, and aromatic residues near the ends of membrane-spanning ␣-helices may be determinants of helical tilt within the membrane bilayer. Arginine is the most effective, determining tilt direction and inducing tilt angles as high as 24°in synthetic peptides incorporated into artificial membrane systems.…”
Section: R444lmentioning
confidence: 99%